A delicately designed functional binder enabling in situ construction of 3D cross‐linking robust network for high‐performance Si/graphite composite anode. Issue 12 (6th December 2021) - Liu, Shujian; Cheng, Shaokai; Xie, Ming; Zheng, Yun; Xu, Gaojie; Gao, Shuyu; Li, Jian; Liu, Zhihong; Liu, Xueqing; Liu, Jiyan; Yan, Bo; Yan, Weixiong; et al.
Abstract: The silicon (Si)‐based anodes suffer from large volume expansion in the lithiation process. Aiming at improving the cycling stability of a Si/graphite composite anode processed by chemical vapor deposition (CVD) method, a functional aqueous binder was delicately designed and synthesized via an aqueous copolymerization of lithium acrylate and vinyl triethoxy silane (VTEO). The PAA‐VTEO binder can in situ react with the silanol groups on the surface of Si nanoparticles to form a robust 3D cross‐linked network. The resulting extremely high modulus and hardness of this integrated 3D network structure effectively restrained the volume expansion effect and significantly enhanced the electrochemical cycling stability of the CVD‐Si@graphite composite anode. This work will provide new perspectives in designing functional binder for Si‐based anodes. Abstract :